Temperature, tropes, sun-worship, nudity, German colonies, post-colonial literature - Martin, Ariane (Studia Germanica Posnaniensia, 2015)
The Magic Mountain (1924) relates an account of erotic passion. Both Hans Castorp’s emotional state and the object of his desire are characterised in a thermographic manner. The thermometer, which he buys (or, rather, acquires), is at once a Dingsymbol part of the discourse of desire and a real object common in tuberculosis sanatoria prior to the First World War. Castorp’s temperature of 37.6 degrees Celsius objectively quantifies his subjective sensibility. This specific constellation creates ironic dis-tance in the novel’s tale.